HUBUNGAN KECANDUAN MEDIA SOSIAL DENGAN CYBERBULLYING DI SMKN 4 PADANG TAHUN AJARAN 2025/2026 - Arieasti, Nadya; Rismi, Ridho; Pria Pandri, Desep (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between social media addiction and cyberbullying at SMKN 4 Padang, Academic Year 2025/2026. This study used a quantitative correlational approach. The population of this study was 553 SMKN 4 Padang students enrolled in the 2025/2026 academic year, with a sample of 232 students selected using proportional random sampling. This study examines the relationship between social media addiction and cyberbullying. The instrument used for data collection in this study was a Likert scale questionnaire. Data analysis was performed using statistical software in Microsoft Excel. Based on the data analysis, the hypothesis was obtained with a calculated r value of 0.708, while the table r value was 0.129. Because the calculated r value is greater than the table r value (0.708 > 0.129), the hypothesis is accepted, indicating a positive relationship between social media addiction and cyberbullying among students at SMKN 4 Padang. Therefore, cyberbullying can be reduced by students if social media is used effectively.